The Implementation of the Principal's Academic Supervision in Improving the Professionalism of Early Childhood Educators - Yuningsih, Restu; Andriani, Lia; Warmansyah, Jhoni; Sari, Meliana; Wiliani, Sherly; Solin, Saobil Sobri; Wiska Bela, Sandora (Journal of Islamic Education Students (JIES), 2024)
The purpose of this study was to determine the implementation of academicsupervision of principals in improving the professionalism of PAUD teachers. Thetype of research used in this research is descriptive qualitative. The data sources inthis study were the principal and three teachers. The data collection techniques usedwere interviews and field notes. Data analysis by reducing data, presenting data,and verifying data. The research findings indicate that school principals mentorteachers to enhance their professionalism, improve their knowledge and skills, andenhance the quality of education. Inhibiting factors include teacher absenteeismand nervousness during supervision. Supporting factors include positive teacher┬áresponse and good relationships between all parties involved.